2005
DOI: 10.4314/zjer.v15i1.26020
|View full text |Cite
|
Sign up to set email alerts
|

Pupils\' Drawings of What is Inside Themselves: A Case Study in Zimbabwe

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
2
9
0
3
Order By: Relevance
“…This study replicates other similar studies conducted in other parts of the world (Reiss and Tunnicliffe 2001;Reiss et al 2002;Manokore and Reiss 2003) where children were asked to draw what was inside their bodies. The intention was not to use drawings as an assessment tool; rather we wanted to see what learners of this age had learnt about their bodies in an informal way.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study replicates other similar studies conducted in other parts of the world (Reiss and Tunnicliffe 2001;Reiss et al 2002;Manokore and Reiss 2003) where children were asked to draw what was inside their bodies. The intention was not to use drawings as an assessment tool; rather we wanted to see what learners of this age had learnt about their bodies in an informal way.…”
Section: Introductionsupporting
confidence: 81%
“…The method used in this study was adapted from that developed by Reiss and Tunnicliffe (2001) and used in the international study conducted by Reiss et al (2002) and Manokore and Reiss (2003).…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that this kind of description has not been found in the European studies, while it seems to be a common idea among the South African students (Dempster & Stears, 2013). In a smaller study conducted in Zimbabwe (Manokore & Reiss, 2003), the explanatory model involving the lungs was also represented. In this study there was an interesting diversity in the non-scientific descriptions (B category) concerning answers on the drinking of water.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have shown that it is difficult for students to see how the different organ systems are connected (Carvalho, Silva, Lima, Coquet & Clément, 2004;Clément, 2003;Manokore & Reiss, 2003;Prokop & Fancovicova, 2006). The specific questions asked in the data collection intend to obtain information about the level of detail in which students understand the organ systems.…”
Section: Introductionmentioning
confidence: 95%